SISTEM PENDUKUNG KEPUTUSAN GURU BERPRESTASI DI GLOBAL PRIMA NATIONAL PLUS SCHOOL - Siti Aisyah; Nur Siska; Yuni Dame Ria Sinurat; Melissa Melissa; Sugiarto Sugiarto (Politeknik Bisnis Indonesia, 2019)
To support quality education with a purpose to educate the generation of the nation, the thing to note is the quality of a teacher where it serves as a channel for delivering education / the teaching. Therefore, to know the quality, it needs to be held a selection of outstanding teachers with the aim of encouraging and motivating teachers for integrity, ready to compete and high quality. Based on these problems then this study aims to design a system decision support for the selection of outstanding teachers at Global Prima National Plus School Medan. The method used is Simple Additive Weighting (SAW). There are five criteria that the author uses namely Discipline, Achievements, Responsibilities, Initiatives and Presence. The research was conducted with looking for weight values for each criterion, then ranking process which determines the outstanding teacher in the case study.